2015
DOI: 10.1038/ncomms9101
|View full text |Cite
|
Sign up to set email alerts
|

Cas9-Assisted Targeting of CHromosome segments CATCH enables one-step targeted cloning of large gene clusters

Abstract: The cloning of long DNA segments, especially those containing large gene clusters, is of particular importance to synthetic and chemical biology efforts for engineering organisms. While cloning has been a defining tool in molecular biology, the cloning of long genome segments has been challenging. Here we describe a technique that allows the targeted cloning of near-arbitrary, long bacterial genomic sequences of up to 100 kb to be accomplished in a single step. The target genome segment is excised from bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
175
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(177 citation statements)
references
References 37 publications
1
175
0
1
Order By: Relevance
“…This is followed by in vitro digestion of the DNA with the Cas9 enzyme at two sites flanking the locus of interest (Figure 1). We have previously shown that CATCH can be used for efficient cloning of large genomic segments via Gibson assembly (7,8). In the current study we show that the enriched DNA can be analyzed in detail at various genomic scales at reduced complexity and cost relative to whole genome sequencing methods.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Ismentioning
confidence: 83%
“…This is followed by in vitro digestion of the DNA with the Cas9 enzyme at two sites flanking the locus of interest (Figure 1). We have previously shown that CATCH can be used for efficient cloning of large genomic segments via Gibson assembly (7,8). In the current study we show that the enriched DNA can be analyzed in detail at various genomic scales at reduced complexity and cost relative to whole genome sequencing methods.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Ismentioning
confidence: 83%
“…Living organisms provide a vast source of genetic elements that can be directly amplified using PCR from the natural sequences. However, PCR amplification may be challenging, especially for long fragments or from complex templates such as high GC content genomes, highly repetitive sequences, or metagenomic samples, and hence requires continuing technical improvement (Jiang et al, 2015). On the other hand, de novo synthesis starts from oligonucleotide synthesis (a few base-pairs to a couple hundred base-pairs) and then assembled to double-stranded fragments of a few hundred to a couple thousand bps (Chao et al, 2015a; Kosuri and Church, 2014), capable of writing DNA molecules of arbitrary sequences with few constraints.…”
Section: Buildmentioning
confidence: 99%
“…Similarly, yeast-based transformation-associated recombination (TAR) allowed the capture and activation of a 67 kb NRPS cluster from Saccharomonospora in Streptomyces coelicolor to produce a new antimicrobial lipopeptide, taromycin A [65]. Use of the RNA-guided Cas9 nuclease circumvents the requirement for unique restriction sites flanking the target BGCs and facilitates direct cloning of large clusters (up to 100 kb) by Gibson assembly or TAR [66, 67]. Recently, the combined use of TAR with CRISPR/Cas9 in a yeast-based promoter-engineering platform mCRISTAR enabled the efficient multiplex replacement of eight promoters to activate the tetarimycin A cluster in S. albus [68].…”
Section: Accessing Silent Natural Product Gene Clustersmentioning
confidence: 99%